A meta-analysis of breastfeeding and osteoporotic fracture risk in the females. Issue 2 (February 2017) - Duan, X.; Wang, J.; Jiang, X.
Abstract Summary Our meta-analysis included 12 studies from PubMed, Embase, and Web of Science. Finding indicated breastfeeding may well reduce the risk of osteoporotic fracture. Introduction Several epidemiologic studies have investigated that breastfeeding is associated with short-term bone loss in the women, but the long-term effect on osteoporotic fracture risk remains unclear. Thus, we conducted this meta-analysis to explore the potential association between breastfeeding and osteoporotic fracture risk in the females and possible dose-response relationship between them. Methods We searched PubMed, Embase, and Web of Science (ISI) up to April 2016 for relevant articles associated between breastfeeding and osteoporotic fracture. Pooled relative risks (RRs) with 95 % confidence intervals (CIs) were calculated with a random-effects model. Dose-response analysis was performed by restricted cubic spline. Results Twelve articles including 14, 954 participants were identified. The pooled RRs of osteoporotic hip and forearm fracture for the highest vs lowest duration of breastfeeding were 0.84 (95 % CI 0.67–1.05), 0.72 (95 % CI 0.52–0.99), and 0.82 (95 % CI 0.56–1.19), respectively. In subgroup analysis, breastfeeding was associated with a decreased risk of osteoporotic fracture in case-control study (RR = 0.70, 95 % CI 0.49–0.99) and postmenopausal women (RR = 0.66, 95 % CI 0.47–0.93). In dose-response analysis, osteoporotic and hip fracture risk decreased by 0.9 and 1.2 % for each month increment of breastfeeding, respectively. Conclusions Our meta-analysis revealed that breastfeeding may well reduce the risk of osteoporotic fracture. More cohort studies with large sample sizes are needed to confirm the conclusion.